Optimalisasi Produksi Benih Botani Bawang Merah (Allium ascalonicum L) Varietas Bima Brebes di Kepulauan Bangka Belitung - Kartika Kartika; Winda Wahyuni; Eka Sari (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2026)
The use of botanical seeds, better known as True Shallot Seed (TSS), as a seed source for shallot production has technical and economic standards to support the development of shallots in the Bangka Belitung Islands. This research was conducted in a farmer's garden in Central Bangka Regency, with coordinates 2°13'02